Skeletal And Dentoalveolar Components Of Class Iı Correctıon Wıth The Of Actıvator-Occıpıtal Headgear Combınatıon - Tamer Türk; Müfide Dinçer (Turkish Journal of Orthodontics, 2000)

(untitled)
The aim of this study was to evaluate the dentoalveolar and skeletal changes as well as the stability of high angle Class II, division 1 cases treated with the Activator-Occipital Headgear Combination. Twenty-four patients (13 females, 11 males) with an average chronological age of 12 years 1 month were included. Active treatment was performed for an average of 12 months. Retention was carried out for an average of 9 months. One year following retention the material of 17 cases could be obtained. Skeletal and dentoalveolar changes and their contributions to Class II correction were evaluated from 89 lateral cephalograms obtained at the beginning and end of active treatment, end of retention and post-retention. During active treatment the overjet decrease was 5.38 mm. Skeletal and dentoalveolar contributions were 66.9% and 33.1%, respectively. Skeletal contribution arose from the anterior movement of Pg point; dentoalveolar contribution resulted from the posterior movement of the upper incisors. During active treatment the molar correction was 5.54 mm. Skeletal and dentoalveolar contributions were 65% and 35%, respectively. Skeletal contribution resulted from the anterior movement of Pg point, dentoalveolar contribution originated mainly from the posterior movement of the upper molars. During retention and post-retention the upper incisors and molars relapsed close to their pre-treatment position. However, no significant differences in overjet and molar relationship among the treatment phases, except the beginning of treatment, were observed. Anterior movement of Pg point and the posterior movement of the upper incisors were effective in the correction of Class II. During retention and post-retention the upper dentoalveolar structures were responsible for relapse.